Increased macrophage density of cardiac allograft biopsies is associated with antibody‐mediated rejection and alloantibodies to HLA antigens. (11th April 2014) - Xu, Lauren; Collins, Jennifer; Drachenberg, Cinthia; KuKuruga, Debra; Burke, Allen
Abstract Background Antibody‐mediated rejection (AMR) is characterized histologically by intracapillary macrophages. Macrophage density may be an alternative method of determining inflammatory changes in AMR. Methods We identified 118 heart transplant patients with serologic testing for HLA alloantibodies. Macrophage density was graded as 1+ (<45/mm2), 2+ (46–90/mm2), and 3+ (>90/mm2). Maximal macrophage density and complement staining over multiple biopsies were correlated with peak panel reactive antibodies (PRA), donor‐specific antibodies (DSA), and the clinical diagnosis of AMR. Results The presence of PRA correlated with macrophage score (p = 0.001). Macrophage density correlated with any DSA (p < 0.0001), class I DSA (p < 0.0001), class II DSA (p < 0.0001), and class II DQ (p < 0.0001). Nine patients had clinical AMR. Among patients with AMR, 89% had a biopsy over the period of AMR with ≥3+ macrophage density (89% sensitivity); among patients without AMR, 93% of patients had no biopsy at any time with ≥3+ macrophage density (specificity). There was perfect concordance between the scores of C4d positivity and macrophage density in 61% and only partial concordance in 20%, with complete discordance in 19% in biopsies taken during clinical episodes of AMR. Conclusions Macrophage density in allograft endomyocardial biopsies is frequently elevated during clinical episodes of AMR and correlates well with alloantibodies.